The Implementation of Integrative Holistic Early Integrative Early Childhood Development Service and ECE-Post Quality - Sholihatun Sholihatun; Yuli Utanto; Diana Diana (Universitas Negeri Semarang, 2024)
This study aims to find out the overview of the capacity of educators in integrative holistic early childhood development services to quality consisting of education, health, nutrition and care, care, protection and welfare services in the ECE holistic integrative education unit in Jepara Regency. Educator capacity refers to the ability to apply ECE holistic integrative service insights in teaching units. This study uses a descriptive quantitative method with a survey approach. The sample taken in this study was 187 ECE holistic integrative educators in Jepara Regency. The determination of the sample in this study uses a proportional stratification technique because of the stratified sampling. The reason for using this technique is that not all samples have criteria that correspond to the phenomenon being studied. The data collection tool uses a mixed questionnaire through a google form and data analysis using a percentage formula. The results of the study show that the description of the capacity of educators in early childhood development services towards quality has a moderate category. This research suggestion is expected for the Jepara Regency Education Office to provide socialization and form a ECE holistic integrative task force as mandated in Presidential Regulation No. 60 of 2013. For researchers, it is hoped that the next researcher can use an in-depth method and involve many parties such as parents, the Education Office, the Health Office and the Corrections Office to be used as a sample in analyzing the implementation of ECE holistic integrative services in all elements of services, namely education, health, nutrition and care, nurturing, protection and welfare.